Social entrepreneurship and social innovation in ASEAN: Past, present, and future trends - Fauzi, M. A.; Muhamad Tamyez, Puteri Fadzline; Kumar, Senthil (Taylor & Francis, 2022)
Social entrepreneurship and ventures are becoming increasingly important in addressing complex challenges through social innovation. In comparison to traditional entrepreneurship, social entrepreneurship is regarded as a non-typical model and alternative to traditional entrepreneurial ecosystems. The Association of Southeast Asian Nations (ASEAN) region is considered the sixth economic power globally, with a substantial growth of social entrepreneurs. Despite its large potential, there is a considerable gap and focussing on academic and research activities. This study aims to provide a bibliometric review of social entrepreneurship in the ASEAN region. Through a bibliometric approach, 205 journal publications were retrieved from the Web of Science (WoS). Three analyses were performed to explore the most significant publication via citation analysis, mapping the knowledge structure via co-citation analysis, and predicting future trends via co-word analysis. Findings suggest four clusters in the co-citation analysis and five clusters in the co-word analysis. Theoretical and practical implications are presented in developing the potential of social entrepreneurship and social innovation in the ASEAN region.